Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's evaluate each statement one by one, using the given piecewise function:
[tex]\[ f(x) = \begin{cases} -x + 1 & \text{if } x < 0 \\ -2 & \text{if } x = 0 \\ x^2 - 1 & \text{if } x > 0 \end{cases} \][/tex]
### Statement A: \( f(-1) = 2 \)
For \( x = -1 \):
- Since \(-1 < 0\), we use the first case: \( f(x) = -x + 1 \)
- Calculate \( f(-1) \):
[tex]\[ f(-1) = -(-1) + 1 = 1 + 1 = 2 \][/tex]
So, \( f(-1) = 2 \) is true.
### Statement B: \( f(4) = 7 \)
For \( x = 4 \):
- Since \( 4 > 0 \), we use the third case: \( f(x) = x^2 - 1 \)
- Calculate \( f(4) \):
[tex]\[ f(4) = 4^2 - 1 = 16 - 1 = 15 \][/tex]
So, \( f(4) = 7 \) is false. The correct value is \( f(4) = 15 \).
### Statement C: \( f(1) = 0 \)
For \( x = 1 \):
- Since \( 1 > 0 \), we use the third case: \( f(x) = x^2 - 1 \)
- Calculate \( f(1) \):
[tex]\[ f(1) = 1^2 - 1 = 1 - 1 = 0 \][/tex]
So, \( f(1) = 0 \) is true.
### Statement D: \( f(-2) = 0 \)
For \( x = -2 \):
- Since \(-2 < 0\), we use the first case: \( f(x) = -x + 1 \)
- Calculate \( f(-2) \):
[tex]\[ f(-2) = -(-2) + 1 = 2 + 1 = 3 \][/tex]
So, \( f(-2) = 0 \) is false. The correct value is \( f(-2) = 3 \).
### Summary
- Statement A: \( f(-1) = 2 \) is true.
- Statement B: \( f(4) = 7 \) is false (correct value is 15).
- Statement C: \( f(1) = 0 \) is true.
- Statement D: \( f(-2) = 0 \) is false (correct value is 3).
Therefore, the true statements are A and C.
[tex]\[ f(x) = \begin{cases} -x + 1 & \text{if } x < 0 \\ -2 & \text{if } x = 0 \\ x^2 - 1 & \text{if } x > 0 \end{cases} \][/tex]
### Statement A: \( f(-1) = 2 \)
For \( x = -1 \):
- Since \(-1 < 0\), we use the first case: \( f(x) = -x + 1 \)
- Calculate \( f(-1) \):
[tex]\[ f(-1) = -(-1) + 1 = 1 + 1 = 2 \][/tex]
So, \( f(-1) = 2 \) is true.
### Statement B: \( f(4) = 7 \)
For \( x = 4 \):
- Since \( 4 > 0 \), we use the third case: \( f(x) = x^2 - 1 \)
- Calculate \( f(4) \):
[tex]\[ f(4) = 4^2 - 1 = 16 - 1 = 15 \][/tex]
So, \( f(4) = 7 \) is false. The correct value is \( f(4) = 15 \).
### Statement C: \( f(1) = 0 \)
For \( x = 1 \):
- Since \( 1 > 0 \), we use the third case: \( f(x) = x^2 - 1 \)
- Calculate \( f(1) \):
[tex]\[ f(1) = 1^2 - 1 = 1 - 1 = 0 \][/tex]
So, \( f(1) = 0 \) is true.
### Statement D: \( f(-2) = 0 \)
For \( x = -2 \):
- Since \(-2 < 0\), we use the first case: \( f(x) = -x + 1 \)
- Calculate \( f(-2) \):
[tex]\[ f(-2) = -(-2) + 1 = 2 + 1 = 3 \][/tex]
So, \( f(-2) = 0 \) is false. The correct value is \( f(-2) = 3 \).
### Summary
- Statement A: \( f(-1) = 2 \) is true.
- Statement B: \( f(4) = 7 \) is false (correct value is 15).
- Statement C: \( f(1) = 0 \) is true.
- Statement D: \( f(-2) = 0 \) is false (correct value is 3).
Therefore, the true statements are A and C.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.